Air pollution and risk of urinary bladder cancer in a case-control study in Spain. Issue 1 (18th July 2007) - Castaño-Vinyals, Gemma; Cantor, Kenneth P; Malats, Núria; Tardon, Adonina; Garcia-Closas, Reina; Serra, Consol; Carrato, Alfredo; Rothman, Nathaniel; Vermeulen, Roel; Silverman, Debra; Dosemeci, Mustafa; Kogevinas, Manolis
Abstract : Objectives: Air pollution has been associated with an increased risk for lung cancer. We examined whether long-term air pollution is associated with bladder cancer risk. Methods: Information from a case-control study in Spain that included 1219 incident cases and 1271 hospital controls was used. Information on residential history including several indicators of exposure to air pollution and other potential risk factors was collected in a face-to-face computerised personal interview. Odds ratios (OR) and 95% confidence intervals (95% CI) were adjusted for age, gender, region, smoking, occupation, water contaminants and diet. Results: Living more than 40 years in a city with a population of more than 100 000 was associated with an increased risk for bladder cancer overall (OR 1.30, 95% CI 1.04 to 1.63). Emissions of polycyclic aromatic hydrocarbons and diesel from industries near the residence, as evaluated by experts, were associated with an increased risk (OR 1.29, 95% CI 0.85 to 1.98), while lower or no excess risks were observed for other pollution-related variables. Odds ratios among never smokers tended to be higher than among smokers. Conclusions: The small to moderate positive associations found for several indices of air pollution and bladder cancer, while suggestive of excess risk, require further evaluation in other settings.